Spectrum-Sharing Transmission Capacity - Jemin Lee; Andrews, J. G.; Daesik Hong (IEEE transactions on wireless communications, 2011)
This paper analyzes spectrum sharing between multiple systems. The efficiency of spectrum sharing is determined primarily by interference, which is a function of the spatial densities of the transmitters in systems dependent on the chosen spectrum sharing method. One method is underlay, which allows all systems to concurrently use the whole spectrum, and the other is overlay, in which a system only utilizes its own assigned spectrum. We define the spectrum-sharing transmission capacity (S-TC) as the number of successful transmissions per unit area subject to outage probability constraints for each system. To prevent some systems from monopolizing access to the spectrum, we also propose a fair coexistence constraint and derive the optimal spatial densities and relative transmission powers both with and without this constraint in terms of the sum S-TC. Through analytical results, the overlay and underlay methods are compared, verifying that the overlay method is generally preferred, and the underlay method is equally good only for optimal transmission power ratios under a fair coexistence constraint.